(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article provides an in-depth analysis of the pedagogical and psychological essence of the differentiated approach and its scientific interpretation in modern education. The role of differentiated instruction in improving learning effectiveness and considering learners’ individual psychological characteristics is substantiated through scholarly sources. The didactic principles, types, and implementation mechanisms of differentiated education are examined from pedagogical and psychological perspectives. The interrelation of differentiated approach with learner-centered education, competency-based learning, and inclusive education is also discussed. The findings contribute to the theoretical and practical development of differentiated teaching strategies.